2,5-dioxido-1,4-benzoquinonediimine (H2L2-), a hydrogen-bonding noninnocent bridging ligand related to aminated topaquinone: different oxidation state distributions in complexes [(bpy)(2)Ru(2)(mu-H2L)](n) (n=0,+,2+,3+,4+) and [(acac)(2)Ru(2)(mu-H2L)] - Kar, S.; Sarkar, B.; Ghumaan, Sandeep; Janardanan, D.; van Slageren, J.; Fiedler, Jan; Puranik, Vedavati G.; Sunoj, R. B.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry - a European Journal, 2005)
{The symmetrically dinuclear title compounds were isolated as diamagnetic [(bpy)(2)Ru(mu-H2L)Ru(bpy)(2)]- (ClO4)(2) (1-(ClO4)(2)) and as paramagnetic [(acac)(2)Ru(mu-H2L)Ru(acac)(2)] (2) complexes (bpy = 2,2'-bipyridine; acac(-) -
Keywords: bridging ligands; Density functional calculations; EPR spectroscopy; N; O ligands; ruthenium

Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz)-derived [Ru-II(tptz)(acac)(CH3CN)](+) and mixed-valent [(acac)(2)Ru-III(mu-tptz-H+)(-)Ru-II(acac)(CH3CN)](+) - Ghumaan, Sandeep; Kar, S.; Mobin, Shaikh M.; Harish, B.; Puranik, Vedavati G.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
Mononuclear [Ru-II(tptz)(acac:)(CH3CN)]ClO4 ((ClO4)-Cl-[1]) and mixed-valent dinuclear [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(CH3CN)]ClO4 ([5]ClO4; acac = acetylacetonate) complexes have been synthesized via the reactions of Ru-II(acac)2(CH3CN)(2) and 2,4,6-tris(2-pyridyl)-1,3,5-triazine (tptz), in 1:1 and 2:1 molar ratios, respectively. In [1]ClO4, tptz binds with the Ru-II ion in a tridentate N,N,N mode (motif A), whereas in [5]ClO4, tptz: bridges the metal ions unsymmetrically via the tridentate neutral N,N,N mode with the Ru-II center and cyclometalated N,C- state with the Ru-III site (motif F). The activation of the coordinated nitrile function in [1]ClO4 and [5]ClO4 in the presence of ethanol and alkylamine leads to the formation of iminoester ([2]ClO4 and [7]ClO4) and amidine ([4]ClO4) derivatives, respectively. Crystal structure analysis of [2]ClO4 reveals the formation of a beautiful eight-membered water cluster having a chair conformation. The cluster is H-bonded to the pendant pyridyl ring N of tptz and also with the O atom of the perchlorate ion, which, in turn, makes short (C-H––-O) contacts with the neighboring molecule, leading to a H-bonding network. The redox potentials corresponding to the (RuI)-I-I state in both the mononuclear {[(acac)(tptz)Ru-II-N=-C-CH3]ClO4 ([1]ClO4) >> [(acac)(tptz)Ru-II-NH=C(CH3)-OC2H5]ClO4 ([2]ClO4) > [(acac)(tptz)(RuNH2)-N-II-C6H4(CH3)]ClO4 ([3]ClO4) > [(acac)(tptz)Ru-II-NH=C(CH3)-NHC2H5]ClO4 ([4]ClO4)} and dinuclear {[(acac)(2)Ru-III-{mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 {(mu-tptz-H+)(-)}Ru-II(acac)(N equivalent to C-CH3)]ClO4 ([5]ClO4), [(acac)(2)Ru-III[(mu-tptz-H+(N-O ([6]ClO4), [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NH=C(CH3)-OC2H5)]ClO4( [7]ClO4), and [(acac)(2)Ru-III{(mu-tptz-H+)(-)}Ru-II(acac)(NC4H4N)]ClO4 ([8]ClO4), complexes vary systematically depending on the electronic nature of the coordinated sixth ligands. However, potentials involving the Ru-III center in the dinuclear complexes remain more or less invariant. The mixed-valent (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) exhibits high comproportionation constant (K-c) values of 1.1 X 10(12)-2 x 109, with substantial contribution from the donor center asymmetry at the two metal sites. Complexes display Ru-II- and Ru-III-based metal-to-ligand and ligand-to-metal charge-transfer transitions, respectively, in the visible region and ligand-based transitions in the UV region. In spite of reasonably high K, values for [5]ClO4[8]ClO4, the expected intervalence charge-transfer transitions did not resolve in the tpical near-IR region up to 2000 nm. The paramagnetic (RuRuIII)-Ru-II species ([5]ClO4-[8]ClO4) displays rhombic electron paramagnetic resonance (EPR) spectra at 77 K (< g > similar to 2.15 and Delta g similar to 0.5), typical of a low-spin Ru-III ion in a distorted octahedral environment. The one-electron-reduced tptz complexes [RuII(tptz center dot-)(acac)(CH3CN)] (1) and [(acac)(2)Ru-III{mu-tptz-H+)(center dot 2-)}-Ru-II(acac)(CH3CN)] (5), however, show a free-radical-type EPR signal near g = 2.0 with partial metal contribution.

Valence-state analysis through spectroelectrochemistry in a series of quinonoid-bridged diruthenium complexes [(acac)(2)Ru(mu-L)Ru(acac)(2)](n) (n =+2,+1, 0,-1,-2) - Ghumaan, Sandeep; Sarkar, Biprajit; Maji, Somnath; Puranik, Vedavati G.; Fiedler, Jan; Urbanos, Francisco A.; Jimenez-Aparicio, Reyes; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry-A European Journal, 2008)
The quinonoid ligand-bridged diruthenium compounds [(acac)(2)Ru(mu-L2-)Ru(acac)(2)] (acac(-) = acetylacetonato = 2,4-pentanedionato; L2- = 2,5-dioxido-1,4-benzoquinone, 1; 3,6-dichloro-2,5-dioxido-1,4-benzoquinone, 2; 5,8-dioxido-1,4-naphthoquinone, 3; 2-3-dichloro-5,8-dioxido-1,4-naphthoquinone, 4; 1,5-dioxido-9,10-anthraquinone, 5; and 1,5-diimido-9,10-anthraquinone, 6) were prepared and characterized analytically. The crystal structure analysis of 5 in the rac configuration reveals two tris(2,4-pentanedionato)ruthenium moieties with an extended anthracenedione-derived bis(ketoenolatee) pi-conjugated bridging ligand. The weakly antiferro-magnetically coupled {Ru-III(mu-L2-)Ru–(III)} configuration in 1-6 exhibits complicated overall magnetic and EPR responses,. ne simultaneous presence of highly redox-active quinonoid-bridging ligands and of two ruthenium centers capable of adopting the oxidation states +2, +3, and +4 creates a large variety of possible oxidation state combinations. Accordingly. the complexes 1-6 exhibit two reversible one-electron oxidation steps and at least two reversible reduction processes. Shifts to positive potentials were observed on introduction of Cl substituents (1 -> 2, 3 -> 4) or through replacement of NH by O (6 -> 5). The ligand-to-metal charge transfer (LMCT) absorptions in the visible region of the neutral molecules become more intense and shifted to lower energies on stepwise reduction with two electrons. On oxidation, the para-substituted systems 1-4 exhibit monocation intermediates with intervalence charge transfer (IVCT) transitions of (RuRuIV)-Ru-III mixed-valent species. In contrast, the differently substituted systems 5 and 6 show no such near infrared (NIR) absorption. While the first reduction steps are thus assigned to largely ligand-centered processes, the oxidation appears to involve metal-ligand delocalized molecular orbitals with variable degrees of mixing.
Keywords: magnetic properties; quinones; ruthenium; spectroelectrochemistry; structure elucidation; valence-state distributions